La matrogimnasia y el desarrollo psicomotriz de los niños, educación inicial nivel II; escuela Loja año 2014 - Pinzón Ochoa, Danny Patricio (2015)
For the present research work is first fixed direct observation of events that arise on site during daily activities performed principals, administrators, teachers, children and parents, then the surveys were applied to the people who make the educational community and after that the topic of the thesis is formulated: LA PSYCHOMOTOR MATROGIMNASIA AND DEVELOPMENT OF CHILDREN, EARLY EDUCATION LEVEL II, VICENTE SCHOOL BASTIDAS REINOSO, LOJA YEAR 2014. And the problem raised relates to Is poor knowledge of teachers on Matrogimnasia keeps improving family relationships and Psychomotor Development of children and parents? The overall objective was to determine if knowledge about Matrogimnasia improves family relationships and Psychomotor Development of children Level II Early Childhood Education, School Vicente Bastidas Reinoso, Jaramillo Alvarado Clovis neighborhood of the city of Loja, in the 2014. For the development of the thesis methodology was used using the following methods: Deductive, which became a tool for generating scientific knowledge, allowed to determine the sample size and analysis of information elaborate conclusions and the alternative proposal; inductive, was applied to infer criteria, the problem statement and the information of statistical results; analytical, facilitated the analysis of charts and statistical calculations, then reach conclusions and synthetic due analysis was performed, the study population was approximately 54 participants. Among the highlights in the diagnosis results found that teachers and parents have no knowledge of Matrogimnasia, allowing planning and implementing activities Matrogimnasia during the 12 weeks to assess the Pearson correlation coefficient ( r) is 17% improvement in fine motor skills and 54% on their gross motor, the degree of difficulty for children. Among the most important conclusions and recommendations highlight that the program improved Matrogimnasia fine and gross motor skills in children as well as their relationship with their family, requiring more time to get better results, so my main recommendation would include this activity within the curriculum of early education in our country.